SCHOLARLY NETWORKS, DIGITAL RESOURCES AND OPEN ACCESS: CHALLENGES AND LIMITS IN A RESEARCH EXPERIENCE - Ramos, Alejandra; Literas, Luciano; Barbuto, Lorena (Instituto Nacional de Antropología y Pensamiento Latinoamericano, 2024)
The use of new Information Technologies and Communication to promote sharing, participation indiscussions, and collaboration is already common practice in research teams. Our goal is to explorehow the strategic use of digital environments to share inputs and produce knowledge manifests itselfin a case study: the network of researchers who created the database Registros Estatales de Población Indígena de Pampas y Patagonia del siglo XIX (REPIPP). We analyze the forms of conviviality and material support that were required both for the design and implementation of the project and for the communication of its results. We evaluate the characteristics of the case presented in relation to otherpossible articulations and, on this basis, try to contribute to the studies of academic practices from anetwork approach.